2007
DOI: 10.1111/j.1365-2929.2007.02785.x
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a new doctor: a learning or survival exercise?

Abstract: Without the support of senior colleagues who can help the new doctor reflect on quite difficult and uncertain situations, new doctors will almost certainly perceive the first year of the new Foundation Programme as a survival exercise. If new doctors are working in an environment where their learning is properly facilitated, they are more likely to recognise their progress in their professional development and be more proactive in addressing concerns about professional expectations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 7 publications
1
13
1
Order By: Relevance
“…Given that supportive learning climates are considered to be crucial to the quality of PGME (Genn 2001a(Genn , 2001b, we recommend educational practice to include learning climate performance indicators in accreditation standards worldwide. As previous research suggests an association between supportive learning climates and the professional development of residents as caregivers (Cross et al 2006;Brown et al 2007;Dyrbye and Shanafelt 2016), the excellent performing learning climate groups identified in our results would be most desirable for clinical practice. Although it seems intuitive to advice clinical practice to put efforts in achieving excellent learning climates, a study performed by Smirnova et al (2017) warns that too much attention for learning climates may lead to impaired patient outcomes.…”
Section: Implications For Educational and Clinical Practicementioning
confidence: 55%
See 1 more Smart Citation
“…Given that supportive learning climates are considered to be crucial to the quality of PGME (Genn 2001a(Genn , 2001b, we recommend educational practice to include learning climate performance indicators in accreditation standards worldwide. As previous research suggests an association between supportive learning climates and the professional development of residents as caregivers (Cross et al 2006;Brown et al 2007;Dyrbye and Shanafelt 2016), the excellent performing learning climate groups identified in our results would be most desirable for clinical practice. Although it seems intuitive to advice clinical practice to put efforts in achieving excellent learning climates, a study performed by Smirnova et al (2017) warns that too much attention for learning climates may lead to impaired patient outcomes.…”
Section: Implications For Educational and Clinical Practicementioning
confidence: 55%
“…Similarly, international literature stresses that clinical departments' learning climate is crucial to the quality of PGME (Genn 2001a(Genn , 2001bWorld Federation for Medical Education 2003;Weiss et al 2013), using key components of faculties' teaching performance and residents' career satisfaction, learning styles and knowledge (Daugherty et al 1998;Delva et al 2004;Cross et al 2006;Shimizu et al 2013;Lombarts et al 2014) to demonstrate this claim. Research into residents' preparedness for practice and professional development (Cross et al 2006;Brown et al 2007;Dyrbye and Shanafelt 2016) suggests the significance of a supportive learning climate for patient care as provided by residents. It follows that highquality learning climates are of paramount importance to both residents and patients.…”
Section: Introductionmentioning
confidence: 99%
“…of residents with a larger group of clinical supervisors, instead of the single master-apprentice interaction, and the recognition that medical knowledge and skills need to be supplemented by other competencies, such as communication and professionalism, has led to a reorientation of theoretical perspectives on residency learning; notably, the emergence of socio-cultural as well as cognitive accounts of learning (Bleakley 2002;Brown et al 2007). …”
Section: Theoretical Perspectives On Residency Educationmentioning
confidence: 99%
“…A series of research papers, furthermore, highlights the dynamic between medical resident and teacher from the perspective of mentorship (Donovan & Donovan, 2009;Jeffries & Skidmore, 2010;Kilminster & Jolly, 2000' Memon & Memon, 2010Oelschlager, Smith, Tamura, Carline, & Dobie, 2011;Stamm & Buddeberg-Fischer, 2011). Lastly, it is worthwhile to note that this stream of literature also explores the socialization process inherent within the workplace (Hafferty & Hafler, 2011), as residents learn to 'become' practicing physicians (Bleakley, 2011;Brown, Chapman, & Graham, 2007;Foster, 2011) and develop their professional identities (Bleakley, 2011b;Burford, 2012;Helmich & Dornan, 2012) and ways of being (Dall'Alba, 2009). …”
Section: The Medical Contextmentioning
confidence: 99%
“…This is especially relevant given the continual expansion of knowledge developed through medical, clinical and educational science and the application of technology within the context of medicine, particularly within PGME. It has been suggested that becoming a new physician is a survival exercise (Brown et al, 2007). While this is an interesting idea, this mostly relates to the notion of entering the profession, rather than acknowledging the longitudinal aspect of sustaining a career of becoming and being a physician.…”
Section: Instances Of Critical Learning Are Varied and Personalmentioning
confidence: 99%